Strong Synergism of Palmatine and Fluconazole/Itraconazole Against Planktonic and Biofilm Cells of Candida Species and Efflux-Associated Antifungal Mechanism - Wang, Tianming; Shao, Jing; Da, Wenyue; Li, Qianqian; Shi, Gaoxiang; Wu, Daqiang; Wang, Changzhong (Frontiers in Microbiology, 2018)
Fungal infections caused by Candida albicans and non-albicans Candida [NAC] species are becoming a growing threat in immunodeficient population, people with long-term antibiotic treatment and patients enduring kinds of catheter intervention. The resistance to one or more than one conventional antifungal agents contributes greatly to the widespread propagation of Candida infections. The severity of fungal infection requires the discovery of novel antimycotics and the extensive application of combination strategy. In this study, a group of Candida standard and clinical strains including C. albicans as well as several NAC species were employed to evaluate the antifungal potentials of palmatine (PAL) alone and in combination with fluconazole (FLC)/itraconazole (ITR) by microdilution method, checkerboard assay, gram staining, spot assay, and rhodamine 6G efflux test. Subsequently, the expressions of transporter-related genes, namely CDR1, CDR2, MDR1, and FLU1 for C. albicans, CDR1 and MDR1 for Candida tropicalis and Candida parapsilosis, ABC1 and ABC2 for Candida krusei, CDR1, CDR2, and SNQ2 for Candida glabrata were analyzed by qRT-PCR. The susceptibility test showed that PAL presented strong synergism with FLC and ITR with fractional inhibitory concentration index (FICI) in a range of 0.0049–0.75 for PAL+FLC and 0.0059–0.3125 for PAL+ITR in planktonic cells, 0.125–0.375 for PAL+FLC and 0.0938–0.3125 for PAL+ITR in biofilms. The susceptibility results were also confirmed by gram staining and spot assay. After combinations, a vast quantity of rhodamine 6G could not be pumped out as considerably intracellular red fluorescence was accumulated. Meanwhile, the expressions of efflux-associated genes were evaluated and presented varying degrees of inhibition. These results indicated that PAL was a decent antifungal synergist to promote the antifungal efficacy of azoles (such as FLC and ITR), and the underlying antifungal mechanism might be linked with the inhibition of efflux pumps and the elevation of intracellular drug content.